A fast mover! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A new subscriber, Paul Bassey Okon of Macpolykon Agrocare - Farmers Welfare Foundation International in Akwa Ibom State, Nigeria, has already put Spore to work on new business ideas. 'I was really challenged by the Viewpoint in Spore 97 that we...